Influência do bisfosfonato Zometa® (ácido zoledrônico) na osteonecrose de maxilares: revisão de literatura - Garcia Júnior, Nilton Antônio [UNESP] (2011)
Bisphosphonates are used for the diagnosis and treatment of several calcium and bone metabolism disorders. The commercially available drugs are pamidronate, risedronate, alendronate and zoledronic acid. Since 2003, there are reports about a possible association between the use of bisphosphonates and the occurrence of osteonecrosis of the jaws. Although these bone lesions may occur spontaneously, precipitating factors such as surgical trauma and trauma from prosthesis may contribute to the development of osteonecrosis in immuno-compromised patients who are using bisphosphonates. Therefore, several recommendations have been made in regard to the prevention and treatment of osteonecrosis of the jaws. In fact, the risk of developing bisphosphonate induced osteonecrosis of the jaws is related to the cumulative effect of the drug, duration of the therapy, presence of contributing medical conditions and/or preexisting dental disease and invasive dental procedures. New studies are crucial to establish which group of individuals or oral factors may better predict the risk of developing this pathology, as well as the best dosage, route of administration and type of bisphosphonate for different groups of patients. Unfortunately few long term controlled studies have been conducted to evaluate the occurrence of bisphosphonate induced osteonecrosis of the jaws. The aim of this study was to review the current evidences about the influence of the use of zoledronic acid (Zometa®) on osteonecrosis of the jaws